Plasma adsorption in refractory chronic gouty arthritis flare: A case report - Lei, Yan; Cui, Tian-Jiao; Wang, Xiao-Hua; Zhang, Xue-Mei; Tang, Chun; Zheng, Zhi-Hua (Frontiers in Immunology, 2022)
Background Along with uric acid, which is the primary driving factor of gout, downstream inflammatory mediators have been shown to be involved in the pathogenesis of gouty arthritis flares. Extracorporeal haemadsorption is an emerging technology for the treatment of dysregulated inflammatory states by effectively removing cytokines from the bloodstream. Whether haemadsorption was effective in refractory gout flares has not been reported in the literature. Case summary We report the case of a 52-year-old male who presented with refractory gouty arthropathy for 30 years. His uric acid levels were poorly controlled due to poor diet and treatment compliance. Tophi were found to have precipitated in multiple joints and subcutaneous tissue. In the last 2 years, his incidents of gouty flares had become more frequent, and resistant to the medications, including colchicine, allopurinol, febuxostat, glucocorticoids, and NSAID analgesics. He had experienced a triad of chills, high fever and arthritis for the past 2 weeks. Therefore, he took 2 mg colchicine twice daily for 2 weeks with no improvement in his pain. Proinflammatory cytokines, such as interleukin-6 (IL-6) and tumour necrosis factor-α (TNF-α), were found to be remarkably elevated. Given that conventional treatment was unsuccessful, we tried to employ plasma adsorption (PA) to remove inflammatory cytokines. After 4 sessions, symptoms, such as fever, joint swelling and pain, were greatly improved. Meanwhile, the levels of proinflammatory factors such as IL-6 and TNF-α were found to be decreased, while the anti-inflammatory factor IL-10 remained the same during the course. He was followed up for 8 months and arthritis have flared up twice in response to a high-purine diet. Conclusion Our study suggests that plasma adsorption (PA) may be a promising and feasible treatment for refractory gout when conventional treatments are unsatisfactory or contraindicated. However, more clinical trials are needed to verify the efficacy and safety of the treatment.